2013
DOI: 10.1016/j.jcmg.2012.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Stress Echocardiography to Assess Stenosis Severity and Predict Outcome in Patients With Paradoxical Low-Flow, Low-Gradient Aortic Stenosis and Preserved LVEF

Abstract: The objective of this study was to examine the value of stress-echocardiography in patients with paradoxical low-flow, low-gradient (PLFLG) aortic stenosis (AS). The projected aortic valve area (AVAProj) at a normal flow rate was calculated in 55 patients with PLFLG AS. In the subset of patients (n = 13) who underwent an aortic valve replacement within 3 months after stress echocardiography, AVA(Proj) correlated better with the valve weight compared to traditional resting and stress echocardiographic parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
98
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(111 citation statements)
references
References 6 publications
7
98
0
6
Order By: Relevance
“…However, cut points for determining truly severe AS based on a change in AVA and gradient with pharmacological intervention are not uniform across studies and require further investigation. 15,16 Even so, the current data provide further support for the concept that systemic HTN can influence the evaluation of AS severity. …”
supporting
confidence: 64%
“…However, cut points for determining truly severe AS based on a change in AVA and gradient with pharmacological intervention are not uniform across studies and require further investigation. 15,16 Even so, the current data provide further support for the concept that systemic HTN can influence the evaluation of AS severity. …”
supporting
confidence: 64%
“…Thus, we were not able to estimate contractile reserve, which is known to affect the outcome of patients with cLF‐LG 31. Only little is known about the role of dobutamine stress echocardiography in pLF‐LG 33. The assessment of calcium score has gained increasing importance in the diagnosis of LF‐LG because the degree of valve calcification by computed tomography is related to AS severity and outcome.…”
Section: Discussionmentioning
confidence: 98%
“…Clavel et al reported a validation study of dobutamine stress echocardiography for LFLPG severe AS with preserved LVEF, and revealed that approximately 30% of LFLPG severe AS patients had pseudo-severe AS, and therefore a good prognosis, though the authors did not clarify the characteristics or entities of pseudo-severe AS. 9 Complicating conditions may contribute to the clinical relevance of pseudosevere AS in LFLPG severe AS with normal LVEF; reduced SV with small LV size, measurement errors in estimating LV SV or AVA, conditions during echocardiographic examinations, or inconsistencies in the definition of severe AS in current guidelines. 20, 21 In the present study, there was no difference between LFLPG severe AS with preserved GLS and impaired GLS in the prevalence of comorbid CAD or prior MI and CABG, which may affect intrinsic myocardial function.…”
Section: Discussionmentioning
confidence: 99%